2020
DOI: 10.2144/fsoa-2019-0132
|View full text |Cite
|
Sign up to set email alerts
|

Does thiol/disulfide Homeostasis Affect the Number of Metaphase 2 Oocyte in the Treatment of In Vitro fertilization?

Abstract: Aim: To investigate the effect of thiol/disulfide homeostasis on the number of oocytes retrieved and metaphase 2 (M2) oocytes in patients undergoing in vitro fertilization. Method: A prospective study of 94 patients who were admitted to the in vitro fertilization clinic was conducted. Serum samples were taken on the oocyte pick-up day and kept until the analysis. Thiol and disulfide were measured in order to evaluate the total thiol/disulfide. Results: A statistically significant correlation was observed betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Contrarily, Yildirim et al showed increased serum thiol levels and decreased disulfide levels in PCOS patients, and the discrepancy between the results might be due to the type of samples as FF used in a study by Tola et al [ 20 ]. In addition, Özdemir et al demonstrated that the serum thiol/disulfide homeostasis did not differ among patients with male factor infertility, unexplained infertility, and DOR [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrarily, Yildirim et al showed increased serum thiol levels and decreased disulfide levels in PCOS patients, and the discrepancy between the results might be due to the type of samples as FF used in a study by Tola et al [ 20 ]. In addition, Özdemir et al demonstrated that the serum thiol/disulfide homeostasis did not differ among patients with male factor infertility, unexplained infertility, and DOR [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, BQS showed a negative correlation with FF oxidant parameters and did not show any correlation with serum oxidants. In contrast, Özdemir et al revealed that the increased serum disulfide levels had a positive correlation with MII oocytes and they explained this finding by the necessity of a small amount of OS for oocyte development [ 21 ]. In folliculogenesis, the FF microenvironment was more pivotal than that of serum.…”
Section: Discussionmentioning
confidence: 99%